The influence of crusher speed on extra virgin olive oil characteristics. Issue 1 (21st June 2016) - Guerrini, Lorenzo; Migliorini, Marzia; Giusti, Matteo; Parenti, Alessandro
Abstract : Milling is an aspect of olive oil production that has received very little attention, and there have been very few studies of the relationship between crusher speed and oil quality. This work compares the effect of three blade cutter crusher speeds used in an industrial plant on the main olive oil chemical and sensory parameters, at two points in time: immediately post‐production, and after eight month of storage. The ANOVA results showed that faster crushing significantly increases chlorophyll and total biophenol content. Secoiridoids are particularly affected and concentrations of 3, 4‐DHPEA‐EDA and p‐DHPEA‐EDA significantly varied in oils milled at different speeds. From the lowest to the highest speed a difference of roughly 50 mg/kg (on about 400 mg/kg) for total biophenols, and about 40 mg/kg of 3, 4‐DHPEA‐EDA is found. Panel testing found higher bitterness and astringency scores in oils produced at the higher speed. These findings suggest that crushing speed can be used to characterize olive oils. Practical applications: Crushing speed is easy to change in olive mills, and could be used to control the sensory and nutraceutical profile of extra virgin olive oil through its effect on bitterness, astringency, and phenolic content parameters. Hence, it is very useful to have a better understanding of the relationship between crushing speed and olive oil characteristics. Crushing speed can be used to characterize olive oils. Faster crushing significantly increases chlorophyll, total biophenol, 3, 4‐DHPEA‐EDA, and p‐DHPEA‐EDA. Panel testing found higher bitterness and astringency scores in oils produced at the higher speed. Abstract : Crushing speed can be used to characterize olive oils. Faster crushing significantly increases chlorophyll, total biophenol, 3, 4‐DHPEA‐EDA, and p‐DHPEA‐EDA. Panel testing found higher bitterness and astringency scores in oils produced at the higher speed.